The Role Of Indonesian Women Soldiers As Peacekeeping Operations (Women Peacekeeper) In Maintaining World Peace - Muhammad Adham Pradhana; Bambang Wahyudi; Yulian Azhari; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
After the adoption of UN Security Council Resolution 1325 in 2000, the United Nations (UN) created the Women, Peace, and Security (WPS) mandate to promote gender equality and enable women's full participation in global security and peacekeeping efforts. The aim of this mandate is to ensure that women have equal access to opportunities, resources, and services, as well as the ability to participate in decision-making processes, in order to build and maintain peace and security. This research aims to analyze the role of the Indonesian Women's Army as Women Peacekeepers in maintaining world peace. In an increasingly complex era of globalization, conflicts and threats to global peace are on the rise. Involving more women in peacekeeping operations is expected to make a significant contribution to maintaining stability and world peace. The research methodology used is a qualitative approach with literature study and analysis of secondary data. This study analyzes the role of the Indonesian Women's Army in peacekeeping operations. The findings of this research indicate that the Indonesian Women's Army, as Women Peacekeepers, play a crucial role in maintaining world peace. They not only contribute to the maintenance of physical security but also play a significant role in empowering women and children, addressing cases of sexual violence, and advocating for gender equality.